2020
DOI: 10.2147/dddt.s249228
|View full text |Cite
|
Sign up to set email alerts
|

<p>Development of 13-Cys-BBR as an Agent Having Dual Action of Anti-Thrombosis and Anti-Inflammation</p>

Abstract: Background: There is a correlation between tumor and inflammation. The activity of 13-[CH 2 CO-Cys(Bzl)-OBzl]-berberine (13-Cys-BBR) slowing tumor growth is higher than that of BBR. Whether the anti-inflammation activity of 13-Cys-BBR is higher than that of BBR remains unknown. There is a correlation between thrombosis and inflammation. Whether 13-Cys-BBR is an inhibitor of thrombosis remains unknown. Purpose: The object of this investigation is to compare the activities of 13-Cys-BBR inhibiting thrombosis and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…On the other hand, regulatory T cells (Treg) are anti-inflammatory cells that secret anti-inflammatory cytokines such as IL-10, IL-35, IL-10, and tumor growth factor-beta (TGF-β), thereby inhibiting Th1/Th17 immune response and counterbalance of the inflammatory response (Li et al 2020a , b ). Treg cells are often defective in autoimmune disorders and viral infections (Shimokawa et al 2020 ; Wan et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, regulatory T cells (Treg) are anti-inflammatory cells that secret anti-inflammatory cytokines such as IL-10, IL-35, IL-10, and tumor growth factor-beta (TGF-β), thereby inhibiting Th1/Th17 immune response and counterbalance of the inflammatory response (Li et al 2020a , b ). Treg cells are often defective in autoimmune disorders and viral infections (Shimokawa et al 2020 ; Wan et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that BBR may prevent thrombosis and assist thrombolysis by streptokinase and urokinase (Aid, Busman-Sahay et al 2020 ). A recent in vitro study demonstrated that BBR and its derivative 13-Cys-BBR inhibit inflammation-induced thrombosis (Li et al 2020a , b ). Gao et al observed that BBR decreases lipopolysaccharide (LPS)-induced activation of tissue factor procoagulant activity (Gao et al 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…The physiological functions of BAPs are diverse, such as hormone effects, 4 immune regulation, 5 antithrombosis, 6 antihypertension, 7 cholesterol‐lowering, 8 antibacterial, 9 antiviral, 10 and anticancer effects 11 . These functions are unique physiological functions that the original protein or constituent amino acids do not possess, and the constituent amino acids of many active peptides are not necessarily essential 12 .…”
Section: Introductionmentioning
confidence: 99%
“…(3) Separation of functional peptides and development of analytical techniques, especially high-sensitivity, simple, and easy target peptide activity analysis and detection systems and analytical techniques 21 ; (4) Research on functional biological evaluation of peptides 22 ; (5) Development of bioactive peptide medicines and functional foods 23 ; (6) Engineering research on low-cost, highpurity, and mass production of bioactive peptides 24 ; (7) Application research of bioengineering technology in the preparation of active peptides, such as protein engineering, 25 enzyme engineering, 26 genetic engineering, 27 cell culture technology, 28 and so forth.…”
mentioning
confidence: 99%